Hard Skill-Based Village Administration Management in the Coastal Area Community of Bilato Village, Gorontalo District, Gorontalo Province - Arwildayanto2; Novianty Djafri; Sukma Nurilawati Botutihe; Apriyanto A.J Pauweni (Institute of Computer Science (IOCS), 2020)
The aim of the activity is to increase the development of the village administration management by increasing the capacity of hard skills for the purpose of implementing activities are; The Village Government, namely the Bilato Village Apparatus, as well as the Bilato community as consumers who receive services from the Bilato Village Officials. Bilato Sub-District, Gorontalo District, Gorontalo Province. Activity Implementation Methods are; Survey method, in the form of technical assistance for implementation; Education and Training (DikLat) of Village Officials. through the Focus Group Disscusion (FGD). Data collection techniques, through; observation and documentation and using data analysis techniques; Primary data and secondary data (direct data sources for village officials and literature review searches), descriptive data presentation. The results of the activities are; Management Pattern Model for Character Development of Bilato Village Officials Based on Hard Skills in the Coastal Area of Bilato Sub-District, Gorontalo District, Gorontalo Province; with management; 1) Optimizing the Duties and Functions of the Bilato Village Officials 2) Improving the Village Apparatus Public Service for the People of the Bilato Village Coastal Zone. 3). Understanding Government Policy in; Organizing Village administration (village development and planning; proposing a 'design, aiming to advance the economy of the village community, overcoming gaps), Village financial management and reporting.